If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 2) + -2x + 4 = x + 5 Reorder the terms: 3(2 + x) + -2x + 4 = x + 5 (2 * 3 + x * 3) + -2x + 4 = x + 5 (6 + 3x) + -2x + 4 = x + 5 Reorder the terms: 6 + 4 + 3x + -2x = x + 5 Combine like terms: 6 + 4 = 10 10 + 3x + -2x = x + 5 Combine like terms: 3x + -2x = 1x 10 + 1x = x + 5 Reorder the terms: 10 + 1x = 5 + x Solving 10 + 1x = 5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 10 + 1x + -1x = 5 + x + -1x Combine like terms: 1x + -1x = 0 10 + 0 = 5 + x + -1x 10 = 5 + x + -1x Combine like terms: x + -1x = 0 10 = 5 + 0 10 = 5 Add '-10' to each side of the equation. 10 + -10 = 5 + -10 Combine like terms: 10 + -10 = 0 0 = 5 + -10 Combine like terms: 5 + -10 = -5 0 = -5 Simplifying 0 = -5 Combine like terms: 0 + 5 = 5 5 = -5 + 5 Combine like terms: -5 + 5 = 0 5 = 0 The solution to this equation could not be determined.
| (8x-18)+(7x-31)=(13x-9)+(19x-6) | | 12z-9-10z+3-8=z-9+3z+10-10z | | 8x+2x-3x-2x= | | 8x+1=23 | | 5m-10n=2 | | 3a+6b+3c= | | 8x=10+x | | -n-2u=5-n | | 9x+14=-40 | | 15x-3y=-18 | | n/7=12/42 | | -5X-7Y=-70solvey | | (x+2)(x+3)=(x+7)(x-4) | | -5X-7y=-70 | | 3(t+2)+4(t-1)=72 | | 16+6z=-8 | | 3log^7x=9 | | -25y^2-60y+60= | | d/33 | | -109/3 | | F(x)=4x^2-24x+20 | | t/4-7=16 | | 6x+7=-48-5x | | x^2-2.8x=9 | | 3s-15=-15 | | 5x^2-9x-7=0 | | x/4=21/36 | | -8+5t=-6 | | 7+91x=52x+16 | | 40-2x=8-10x | | 1/2/5/4 | | 8m+6=28 |